A study on Wolbachia-dengue-carrying Aedes mosquitoes (Diptera: Culicidae) focuses on the sustainability and frequency of Wolbachia in high-rise buildings in Selangor, Malaysia - Muhammad Aidil, Roslan; Romano, Ngui; Mas-Azlindah-Ayu, Abd Karim; Ummi Syafiqah, Rosmini; Poon, Soon Ong; Mas Ayu, Ahmad; Yvonne Ai Lian, Lim; Wan Yusoff, Wan Sulaiman (Springer Nature, 2024)
The challenge of dengue control due to the unavailability of a specific medication stresses the importance of releasing Wolbachia-carrying mosquitoes through vector control programs. This study investigated the sustainability and frequency of Wolbachia in Wolbachia-dengue-carrying mosquitoes in two dengue hotspot localities in Selangor. A modified sticky ovitrap was used to collect adult mosquitoes in two Wolbachia-releasing areas in Selangor, Kelana Puteri and Kelana D'Putera condominiums. All mosquito samples were subjected to PCR using wsp-specific primers for Wolbachia detection. Dengue virus was detected using RT-PCR, followed by multiplex-PCR. Out of the 80 Aedes spp. collected, Ae. aegypti was the most predominant species. More than one-third of Ae. aegypti were positive for Wolbachia, with 22.9% being superinfected with both Wolbachia A and B strains. About 61.4% of the species were uninfected with Wolbachia. Ae. aegypti carrying the Wolbachia A strain was also identified, which has previously never been reported. This strain was similar to the one found naturally in Ae. albopictus. None of the Ae. aegypti and Ae. albopictus were positive for dengue virus. This study could serve as a model for local researchers or health authorities to design and plan an effective field release and monitoring of Wolbachia-infected mosquitoes.